Assessing Engagement in Chinese Upper Secondary School Students Using the Chinese Version of the Schoolwork Engagement Inventory: Energy, Dedication, and Absorption (CEDA) - Teuber, Ziwen; Tang, Xin; Salmela-Aro, Katariina; Wild, Elke (Frontiers in Psychology, 2021)
The schoolwork engagement inventory: Energy, Dedication, and Absorption (EDA) is a measure of students' engagement in schoolwork and has been demonstrated valid in Western student populations. In this study, we adapted this inventory to and tested its psychometric appropriates in Chinese upper secondary school students (CEDA). Participants were 1,527 general high school students and 850 vocational high school students. The mean age of the total sample was 16.21 years (54.4% females, age span: 15–19 years). The results of confirmatory factor analyses (CFA) showed that a modified one-factor model fitted the data best. The results of the multigroup CFA showed that the factor structure was metrically invariant across school tracks (i.e., general or vocational high school) and scalarly invariant across gender and school types (i.e., ordinary or key school). Moreover, schoolwork engagement was negatively related to emotional exhaustion and positively related to self-efficacy, perseverance of effort, teacher–student relationships, and life satisfaction. Overall, the CEDA can be regarded as a valid measure for the assessment of student engagement in the Chinese upper secondary school context.